When Mickey Loses Face: Recontextualization, Semantic Fit, and the Semiotics of Foreignness - Brannen, Mary Yoko (Academy of Management Review, 2004)
Foreignness is generally viewed as a liability for the multinational enterprise, negatively affecting strategic fit and the successful transfer of firm assets abroad. Using semiotics—the study of how language systems convey meaning—and the Walt Disney Company's experiences in internationalization, I develop the notion of semantic fit as a necessary complement to strategic fit and formalize a conceptual model of recontextualization—the process by which firm assets take on new meanings in distinct cultural environments.